1994
DOI: 10.1165/ajrcmb.11.4.7917308
|View full text |Cite
|
Sign up to set email alerts
|

Differential expressions of surfactant protein SP-A, SP-B, and SP-C mRNAs in rats with streptozotocin-induced diabetes demonstrated by in situ hybridization.

Abstract: We have previously demonstrated by in situ hybridization and Northern blot analysis that alveolar type II cells and nonciliated bronchiolar epithelial (Clara) cells in lungs of rats with diabetes have decreased surfactant protein A (SP-A) but increased mRNA. In the present study, we have examined the mRNA expression and localization of two hydrophobic surfactant proteins, SP-B and SP-C, and have compared them with SP-A mRNA levels and cellular localization in streptozotocin-induced diabetic lungs. Localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
21
0
2
Order By: Relevance
“…Sugahara et al (22) studied SP-A mRNA in streptozotocin-induced diabetic rats and observed increased SP-A mRNA in alveolar type II cells and Clara cells from diabetic lungs compared with those from control lungs. The relative abundance of SP-A mRNA increased approximately twofold in bronchiolar epithelial cells of diabetic lungs above that in controls (23).…”
Section: Ferná Ndez-real and Associatesmentioning
confidence: 77%
“…Sugahara et al (22) studied SP-A mRNA in streptozotocin-induced diabetic rats and observed increased SP-A mRNA in alveolar type II cells and Clara cells from diabetic lungs compared with those from control lungs. The relative abundance of SP-A mRNA increased approximately twofold in bronchiolar epithelial cells of diabetic lungs above that in controls (23).…”
Section: Ferná Ndez-real and Associatesmentioning
confidence: 77%
“…In this assay, the highest precision was obtained at a sample dilution rate of 1:20 (data not shown). Normally, SP-D is only present in alveoli [17]. However, when the permeability of the alveoli increases as a result of damage, it appears to leak out into the bloodstream [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the elevated SP-A protein levels in the lungs of hyperglycemic rats under oxidative stress can reflect their overproduction and protective effects on the alveolar epithelium. Insulin treatment restored alterations, such as the disrupted ultrastructure of AECII, reduced surfactant biosynthesis, and impaired secretion of surfactant in STZ-hyperglycemic rats (Sugahara et al, 1992(Sugahara et al, , 1994. In the present study, on one hand, the effect of chard on SP was evaluated for the first time.…”
Section: Discussionmentioning
confidence: 82%
“…SP-A mRNA transcription was considerably enhanced in the lungs of the STZ-treated diabetic rats, but immunohistochemical labeling of SP-A in AECII was weak compared with the control lungs (Sugahara et al, 1994). SP-C transcription, however, declined in the STZ-treated diabetic rats (Sugahara et al, 1992).…”
Section: Discussionmentioning
confidence: 84%